1997
DOI: 10.1063/1.120223
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a crystalline phase in amorphous hydrogenated carbon-germanium films by electron beam irradiation

Abstract: The influence of electron beam irradiation on morphology of plasma deposited amorphous hydrogenated carbon-germanium films produced from tetramethylgermanium in a three-electrode af reactor has been studied. It has been found that the insulating films are insensitive to this treatment, whereas a crystalline phase occurs in the semiconducting films. Although the molar content of germanium in these films amounts only to about 0.2, the crystalline phase is composed of pure germanium nanocrystals which contain abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Although it was clearly shown that a-S samples were more cross-linked, no rapid changes in the chemical structure between a-S and a-I, contrary to their electronic structure, were also observed . Similarly, investigations performed by the transmission (TEM) and scanning (SEM) electron microscopy as well as by the electron diffraction have not revealed any differences in the supermolecular structure between the a-I and a-S films . A certain confirmation of the a-I−a-S transition, from the supermolecular structure point of view, has been given, however, by the atomic force microscopy (ATM) and unconventional analysis of XPS spectra …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although it was clearly shown that a-S samples were more cross-linked, no rapid changes in the chemical structure between a-S and a-I, contrary to their electronic structure, were also observed . Similarly, investigations performed by the transmission (TEM) and scanning (SEM) electron microscopy as well as by the electron diffraction have not revealed any differences in the supermolecular structure between the a-I and a-S films . A certain confirmation of the a-I−a-S transition, from the supermolecular structure point of view, has been given, however, by the atomic force microscopy (ATM) and unconventional analysis of XPS spectra …”
Section: Introductionmentioning
confidence: 92%
“…3 Similarly, inves- tigations performed by the transmission (TEM) and scanning (SEM) electron microscopy as well as by the electron diffraction have not revealed any differences in the supermolecular structure between the a-I and a-S films. 5 A certain confirmation of the a-I-a-S transition, from the supermolecular structure point of view, has been given, however, by the atomic force microscopy (ATM) and unconventional analysis of XPS spectra. 4 These measurements indicate that a-Ge X C Y :H films have a nonhomogeneous distribution of charge that step changes between the a-I and a-S forms.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of formation of a crystalline phase in amorphous materials upon electron beam irradiation has been already described for hydrogenated carbon−germanium films produced by plasma deposition in a three-electrode reactor . It has been found that the crystalline phase of these films is composed of pure germanium nanocrystals.…”
Section: Resultsmentioning
confidence: 93%
“…electrical conductivity at room temperature changes more than 15 orders of magnitude. At the same time no rapid change in chemical constitution is observed [3,7,8]. Detailed analysis performed by means of chemical microanalysis, electron spectroscopies (XPS and Auger) and FTIR spectroscopy revealed that chemical structure is practically unchanged when step change in electronic structure occurs [3,9].…”
Section: Introductionmentioning
confidence: 93%